Information Processing Analysis of the Harbor Nautical Charts and Their Representation of the Changes in the Territory: the Case of La Plata Port - Stubbs, Edgardo; Claudia Carut (European Journal of Multidisciplinary Studies, 2017)
Nautical charts are a representation of a territorial moment. Understanding the territory as a state of the process of social construction, historical analysis of the nautical charts allows the understanding of the spatial transformations that has crossed a maritime territory. Thus, the study of them represents a tool for the understanding of territorial transformations from the physical-social environment and in their navigation. According to the territory they represent, their scale and the information provided by nautical charts are classified as: general, Sailing, coastal navigation, approach or landfall, and Harbor charts. The latter, which constitute documents that provide important information for different classes of users, are modified as a result of the fact that ports as complex maritime spaces and of great dynamism cause in its coasts and nearby areas important modifications in both the physical and social environment that are reflected in the documents. The information organization and retrieval contained in the nautical charts are essential for access to them. The RDA (Resource for Description and Access) constitute a set of norms for information processing developed from the Librarianship and Information Science. This work will analyze the functionalities of the concepts of work, expression, manifestation and item incorporated to the RDA for the processing of nautical port charts and the possibilities of representation of the changes in the territory that have occurred over time.